A REVIEW on UNDERWATER ACOUSTIC SIGNAL SENSING MANDREL - .R, Noor Ahmed; Junghare, Prashil M; M S, Haresha; N, Manu (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
In this paper, the design of an optical fiber hydrophone with concentric composite mandrel is outlined. The composite mandrel consists of several layers over the hallow diameter. Design specification of fiber optic sensor is based on application and reviewed literature. Mandrel will be designed using Nylon, Aluminum, and Foam. Aluminum is coated because it radically improves the sensitivity of sensor through its superior compliance. The optimum structure of composite mandrel is determined using finite element method (FEM) to analyze the influence of both mandrel properties of Polymer layer and geometry of composite mandrel on the performance of hydrophone. Here, thicknesses of the polymer layer, length of mandrel, inner and outer diameters are the geometrical properties considered for the analysis purpose